Responsiveness of small businesses to corporate income taxation in Canada: A summary of new findings - Josip Lesica (Economic and Social Reports)
Using the universe of firm-level tax returns for Canada, this study examines the responsiveness of small businesses to corporate taxation over the 2001-2019 period. It quantifies the extent to which small businesses in Canada respond to discontinuities in the statutory corporate tax rates, estimates their bunching, and sheds light on real versus reporting responses. The study also contributes to the empirical literature by quantifying the elasticity of corporate taxable income.